2018
DOI: 10.1186/s12885-018-4369-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic angiosarcoma of the breast: case report and systematic review of the literature

Abstract: BackgroundRadiogenic angiosarcoma of the breast (RASB) is a rare late sequela of local irradiation of the breast or chest wall after breast cancer. The prognosis of women with RASB is poor and there is no standardized therapy for this type of malignancy.Case presentationWe present the case of a 54 year old woman with RASB (poorly differentiated angiosarcoma of the left breast; pT1, pNX, M0, L0, V0) and a history of invasive-ductal cancer of the left breast (pT1b, G2, pN0, ER positive, PR positive, HER-2/neu ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 73 publications
1
19
1
8
Order By: Relevance
“…PBA usually occurs to young women without any inducing factor, while SBA is commonly seen in older women who have a history of breast surgery and radiotherapy. PBA is rarely seen in clinical practice and it is predicted that PBA will have a higher morbidity and be more aggressive in the future [35]. Increasing use of breast-conserving surgery leads to increase in the incidence of SBA and among all secondary tumors resulted from radiotherapy, SBA is believed to be the most common one.…”
Section: Introductionmentioning
confidence: 99%
“…PBA usually occurs to young women without any inducing factor, while SBA is commonly seen in older women who have a history of breast surgery and radiotherapy. PBA is rarely seen in clinical practice and it is predicted that PBA will have a higher morbidity and be more aggressive in the future [35]. Increasing use of breast-conserving surgery leads to increase in the incidence of SBA and among all secondary tumors resulted from radiotherapy, SBA is believed to be the most common one.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary angiosarcoma are more likely to be of high-grade (82%) compared to primary angiosarcoma [6]. Literature review shows many reports of secondary post-irradiation angiosarcoma in females to be hormone-receptor positive breast cancers under hormonal therapy [6, 7]. Our case is unique in that the angiosarcoma was of intermediate grade and occurred in hormone-receptor negative patient without any hormonal therapy.…”
Section: Discussionmentioning
confidence: 90%
“…As opposed to primary angiosarcoma of the breast that affects young women, mean patient age at diagnosis of RASB was 70 years and the mean latency period between radiation therapy and diagnosis was 6 years. (3) The pathogenesis of RASB is still unclear. (4) The two largest published case series of RASB, one with 79 cases and another with 95 cases reported that the 5-year disease-free survival (DFS) was 47% and 62.6%, respectively.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Nevertheless, nodules, plaques or patches may also appear. (3) Imaging of angiosarcoma is nonspecific. Mammography and ultrasonography have no pathognomonic features.…”
Section: ❚ Discussionmentioning
confidence: 99%